1999
DOI: 10.1016/s0963-8687(99)00024-4
|View full text |Cite
|
Sign up to set email alerts
|

The relative success of alternative approaches to strategic information systems planning: an empirical analysis

Abstract: Earl's [1993] five approaches indicates that three bear strong similarities to the 'organisational', 'business-led', and 'administrative' approaches, whilst the fourth cluster is related to both Earl's 'method-driven' and 'technological' approaches. An analysis of the relationship between SISP approach and SISP success, demonstrates that the 'organisational approach' is significantly more successful than the other three approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 31 publications
0
78
0
Order By: Relevance
“…This inconsistency mimics the response to Question 15. The expected rating was strongly agree, since SISP is defined by Doherty et al (1999) as an activity that is ongoing and allows companies to set priorities for IS development. This response also resulted in one of the lowest Likert scores.…”
Section: Interpretation Of the Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This inconsistency mimics the response to Question 15. The expected rating was strongly agree, since SISP is defined by Doherty et al (1999) as an activity that is ongoing and allows companies to set priorities for IS development. This response also resulted in one of the lowest Likert scores.…”
Section: Interpretation Of the Resultsmentioning
confidence: 93%
“…The www.sajesbm.com Article no 144 demographic details indicated that this panellist had a matric certificate; therefore, it is understandable that this panellist would not be familiar with such subject specific terms, hence the exception. Remenyi et al (2000) and Doherty et al (1999) define SISP extensively. Based on these definitions, of all the panellists just one did not know what it meant.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The success of such an initiative is also critically dependent on carrying out effective Strategic Information Systems Planning (SISP) by the firm (Galliers, 1991). As the process whereby an organization determines a portfolio of computer-based applications to help it achieve its business objectives (Galliers, 1993;Lederer and Sethi, 1988), SISP focuses on aligning investment in IS with business goals, exploring IT for competitive advantage, directing efficient and effective management of IS resources, and developing technology policies and architectures (Chan and Reich, 2007;Dohertya et al, 1999;Min et al, 1999;Newkirka et al, 2003;Teubner, 2007). Effective SISP will help support innovations in a firm's IT-dependent strategic initiative (Galliers et al, 1998(Galliers et al, , 1995, such as the implementation of Green IT initiatives.…”
Section: It Capital It-enabled Changes In Management Practicesmentioning
confidence: 99%